ä¸¹æˆŽå¸ƒæ‹‰å›½ç«‹å¤§å¦å¸ˆèŒƒå¦é™¢æ±‰è¯ä¸“ä¸š2016å±Šå¦ç”Ÿ å¯¹åŠ¨è¯â€œäº†è§£â€å’Œâ€œç†è§£â€çš„æŽŒæ¡æƒ…å†µåˆ†æž - Natalia, Vania; Thamrin, Lily; Khiong, Bun Yan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractVerb is an important part in Mandarin grammar. â€œLiao Jieâ€ and â€œLi Jieâ€ are include as stative verbs. The definition of those two words are not really different, but the usage are different. It is also because the understandingÂ  are not really different, during the learning activities the student is not understand or not clear about the difference between those two words until create mistake.To find out how the mastery condition of student from Tanjungpura University chinese language education study program batch 2016 for the words of â€œLiao Jieâ€ and â€œLi Jieâ€ , the writer use research test method to know the mastery condition of students and analyze student difficulties towards those two words. The result shows that the mastery condition of student toward â€œLiao Jieâ€ is better than â€œLi Jieâ€. â€œLiao Jieâ€ the percentage is 59% and â€œLi Jieâ€ only 46%. In the analysis of the type of difficulty, the writer found the students mastery is in â€œLiao Jieâ€ means clearly understand and â€œLi Jieâ€ means only understand.Â Keywords : â€œLiao Jieâ€ Â Â Â Â â€œLi Jieâ€ Â Â Â Â Understanding ConditionÂ